Desempeño de las funciones ejecutivas en adultos mayores con diabetes mellitus tipo I y II: revisión sistemática (2021)
The present documentary review aims to investigate the performance of executive functions in older adults between the ages of 65 and 90 with Type I and II Diabetes Mellitus, for this purpose they were used in databases such as: Nature, Science Direct, Scopus and Journals; locating information from different countries.